2021
DOI: 10.1002/jgc4.1437
|View full text |Cite
|
Sign up to set email alerts
|

Interventions aiming to improve informed decision on prenatal screening and testing: A scoping review of the literature

Abstract: Prenatal screening and testing can be a part of perinatal care that allows couples to have information about their babies' health status before birth to manage the pregnancy and make decisions beforehand (Ravitsky, 2017). While prenatal screening assesses a pregnant woman's chance of having a fetus affected by a genetic condition, prenatal testing (or diagnostic testing) determines whether the fetus has a specific genetic condition. The diagnosis of a fetus with a genetic condition allows the couple to make an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…It will also be important to take current societal perceptions and narratives into account as those have a substantial impact on women’s decision processes 10 . A recent scoping review has also demonstrated the importance of providing information to women, and couples, using different types of modalities to improve understanding and knowledge, such as counselling, booklets, and interactive eHealth tools including decision‐making aids 28 …”
Section: Discussionmentioning
confidence: 99%
“…It will also be important to take current societal perceptions and narratives into account as those have a substantial impact on women’s decision processes 10 . A recent scoping review has also demonstrated the importance of providing information to women, and couples, using different types of modalities to improve understanding and knowledge, such as counselling, booklets, and interactive eHealth tools including decision‐making aids 28 …”
Section: Discussionmentioning
confidence: 99%
“…As evidence builds for the utility and efficacy of using genetic information for diagnosis, risk assessment, and management, so does the need to have a genomics‐competent healthcare workforce. Genetics education is delivered in a variety of ways, from local efforts in individual practices and hospitals to national efforts including the development of genetics and genomics competencies for different healthcare professions and levels of training (Cornel, 2019; Sirisena & Dissanayake, 2019; Talwar et al., 2017; Yesilcinar et al., 2021). Given the range in program type and scope, it is difficult to ascertain the professional background of the individuals creating and leading such education programs, but the limited available data suggest that genetic education leaders have subject matter expertise in genetics/genomics but do not necessarily have professional training in education.…”
Section: Educating Health Professionals About Genetics and Genomicsmentioning
confidence: 99%